Effects of CX3CL1 inhibition on murine bleomycin-induced interstitial pneumonia. (September 2020) - Yamada, Soichi; Miyoshi, Shion; Nishio, Junko; Mizutani, Satoshi; Yamada, Zento; Kusunoki, Natsuko; Sato, Hiroshi; Kuboi, Yoshikazu; Hoshino-Negishi, Kana; Ishii, Naoto; Imai, Toshio; Mikami, Tetsuo; et al.
Background: Treatment for interstitial pneumonia (IP) associated with collagen diseases has not been established. There is a need to elucidate the pathogenesis of IP and develop a novel therapy. We aimed to clarify the role of chemokine (C-X3-C motif) ligand 1 (CX3CL1, also known as fractalkine) in IP. Methods: Bleomycin (BLM) was intratracheally administered to C57BL/6 mice to induce IP. For treatment with control Ab or anti-CX3CL1 mAb, the mice were administered either Ab three times per week for 2 weeks from the day of BLM administration until euthanasia. Expressions of CX3CL1 and its unique receptor CX3CR1 in the lung tissue were examined by immunohistochemical analysis. Cellular infiltration and lung fibrosis were evaluated based on hematoxylin-eosin-staining and Sirius red staining of the lung tissue sections, respectively. Bronchoalveolar lavage fluid (BALF) cells were analyzed by flow cytometry. Results: CX3CL1 and CX3CR1 were strongly expressed in the lung tissue from mice with BLM-induced IP (BLM-IP). Treatment with anti-CX3CL1 mAb did not significantly alter inflammatory cell infiltration or fibrosis in the lung tissue. However, the number of M1-like macrophages in BALF was decreased and surface CD3 expression on T cells was increased by anti-CX3CL1 mAb treatment. Conclusions: Inhibition of CX3CL1 decreased inflammatory cells and may attenuate T cell activation in BALF. CX3CL1 inhibitor may have the potential to suppress the infiltration and activation of immune cells in IP.